Prospects of low-cost photometers for colorimetric serum iron concentration determination - Tan A.F.Y.; Talik N.A.; Yap B.K.; Krishnan P.S. (Springer Verlag, 2023)
Biomedical engineering; Body fluids; Color; Colorimeters; Colorimetry; Costs; Photometers; Photometry; Colorimetric methods; Essential elements; Iron concentrations; Iron deficiency; Low costs; Nutritional disorders; Portable; Serum; Iron